Werneria microphylla (Asteraceae, Senecioneae), a new species from the Andean marshes of Peru - Beltran, Hamilton; Leiva, Segundo (Phytotaxa, 2018)
Werneria microphylla is described and illustrated as a remarkable new species from the high Andes of Peru. It is compared with the putatively most closely related species W. pygmaea and W. spathulata. The new species is a tiny perennial herb and the smallest species of the genus. It has been collected from Ancash to Puno departments thriving in Andean marshes.